WHEN CONTEXT MATERS: A MULTI-LEVEL ANALYSIS OF FOOD SECURITY POLICY IMPLEMENTATION IN KOTAWARINGIN TIMUR’S SUB-DISTRICT - Selvia, Fitriana; Widyastuti, Antonia Eka Sari (Universitas Negeri Yogyakarta, 2024)
This study aims to analyze the implementation of food security policies at the sub-district level in Kotawaringin Timur Regency. The research employs a qualitative method with a case study approach across 17 sub-districts. Data were collected through in-depth interviews, field observations, and document analysis. The findings reveal that food security policy implementation varies among sub-districts, influenced by regional characteristics, resource availability, and local leadership. Program Stabilisasi Pasokan dan Harga Pangan (SPHP), Gerakan Pangan Masyarakat (GPM), and Cadangan Pangan Pemerintah Daerah (CPPD) have been implemented with varying levels of effectiveness. Sub-districts with urban characteristics and trading centers demonstrate more effective implementation compared to rural sub-districts. Major challenges include limited human resources, budget constraints, and infrastructure limitations. The study recommends institutional strengthening, integrated information system development, and enhanced stakeholder coordination to improve the effectiveness of food security policy implementation at the sub-district level.